Pengaruh Profitabilitas Terhadap Nilai Perusahaan Dengan Corporate Social Responsibility Sebagai Variabel Moderating : (Studi Pada Perusahaan Cosmetics And Household Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2022) - Resti Maya Sari; Ade Candra (JURNAL ADMINISTRASI BISNIS (JAB), 2024)
Cosmetic and household goods subsector companies listed on the Indonesia Stock Exchange in 2018-2022 will be analyzed on the influence of profitability on company value moderated by corporate social responsibility. Using quantitative methods because the data obtained is in the form of figures originating from annual reports. The sampling technique uses purposive sampling based on consideration of certain criteria. The data analysis technique uses SmartPLS software version 4.0 using the Partial Least Square (PLS) approach. Based on the results of the analysis carried out, profitability has a positive and significant effect on company value. The greater the profitability, the higher the company value. Profitability has a positive and significant effect on company value, moderated by corporate social responsibility (CSR). The greater the profitability which is strengthened by corporate social responsibility (CSR), the greater the company value will increase.